2017
DOI: 10.1038/s41598-017-02168-3
|View full text |Cite
|
Sign up to set email alerts
|

Powder Metallurgy Processing of a WxTaTiVCr High-Entropy Alloy and Its Derivative Alloys for Fusion Material Applications

Abstract: The WxTaTiVCr high-entropy alloy with 32at.% of tungsten (W) and its derivative alloys with 42 to 90at.% of W with in-situ TiC were prepared via the mixing of elemental W, Ta, Ti, V and Cr powders followed by spark plasma sintering for the development of reduced-activation alloys for fusion plasma-facing materials. Characterization of the sintered samples revealed a BCC lattice and a multi-phase structure. The selected-area diffraction patterns confirmed the formation of TiC in the high-entropy alloy and its d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(89 citation statements)
references
References 152 publications
(229 reference statements)
7
82
0
Order By: Relevance
“…High performance of HEA radiation-resistant materials provides a new idea for nuclear materials, and it has been used as the catalyst in the nuclear energy [97,[101][102][103]. Waseem et al [68] considered that the W x TaTiVCr as low/reduced-activation alloys have a promising future for fusion power plants.…”
Section: Irradiation Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…High performance of HEA radiation-resistant materials provides a new idea for nuclear materials, and it has been used as the catalyst in the nuclear energy [97,[101][102][103]. Waseem et al [68] considered that the W x TaTiVCr as low/reduced-activation alloys have a promising future for fusion power plants.…”
Section: Irradiation Propertymentioning
confidence: 99%
“…Although there are more than four or five elements in HEAs [20], they tend to form a relatively-simple phase after solidification, such as FCC [21], BCC, or HCP [23,68] structures. However, with the extensive and deep research on HEAs, it is found that the alloys also contain ordered intermetallics, amorphous and nanocrystalline precipitates [19,47,69].…”
Section: Phase Formationmentioning
confidence: 99%
“…Specifically, refractory metal elements have relatively high melting points (Ti [1946 °C], Ta [3293 °C], V [2202 °C], Cr [2133 °C], Mo [2895 °C], Nb [2750 °C], Zr [2128 °C], Hf [2504 °C]), it is valuable to explore HEAs composed of these elements for high‐temperature applications in nuclear reactors as plasma facing materials (PFMs). Experimentally W x (TaTiVCr) 1− x ( x = 0.30–0.67) alloys have been fabricated and studied . For instance, using the vacuum arc melting technique, HEAs composed of refractory elements (Ti, V, Cr, Ta, or W) are studied .…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, developing the tungsten alloys has always been a hot issue in optimizing the performance of nuclear fusion reactor, so exploring of new tungsten alloys with suitable properties has being done extensively . From viewpoint of improved properties of W‐based alloy with respect to the pure tungsten, multi‐component alloying is beneficial to further improve the properties of tungsten alloy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation